Life style as a risk factor of human Papillomavirus co-infections with Trichomonas vaginalis in female sex workers - Odigie, Efosa Bolaji; Okungbowa, Micheal Awol (Faculty of Medicine, Trisakti University, 2019)
BACKGROUNDAsymptomatic Trichomonas vaginalis (TV) and human papillomavirus (HPV) co-infection is perceived to have a devastating combined effect on victims. Hence, we investigated TV/ HPV co-infection and determined the risk factors associated with it in female sex workers (FSW).METHODSA cross-sectional study was used to recruit 338 subjects from 6 local government areas (LGAs) in Nigeria for 18 months. Agglutination tests for blood samples, and direct and wet examination of urine and vaginal swabs were conducted in the laboratory. Life style of FSWs was surveyed; data were analyzed with Chi-Square test (X2), paired and unpaired t-test and logistic regression analysis with statistical significance set at p< 0.05.RESULTSLife style characteristics were significantly associated with HPV and TV co-infection (pÂ < 0.001). The model explained 49.9% (Nagelkerke R2) of the variance in infections among FSWs and effectively classified 93.2% of cases. Those involved in oral sex were 1.795 times more likely to be infected compared to those not involved (OR: 1.795; 95% C.I.: 1.005 â€“ 33.525; p=0.001). Street and residential FSWs all have increased likelihood of being infected. Hard drug usage was also associated with an increased likelihood of being infected with the disease (OR: 3.582; 95% C.I.: 1.573 - 11.756; p=0.001).CONCLUSIONSLife style (hard drug usage and oral sex practices) was observed in association with HPV/ TV co-infection in FSWs with a preponderance of 49.9%. This study demonstrated the value of screening for genital infections in HPV positive subjects in order to reduce the probable synergistic effects of co-infections.